예비 수학교사의 멘 • 튜터링 활동에 관한 사례 연구 - 허유진; 고호경; 허난 (East Asian Mathematical Journal, 2021)
In this study, a men-tutoring model was applied to four second-year high school students in mathematics learning counseling that could cultivate cognitive and affective domains. By observing and analyzing the cases, we examined the effects of mathematics learning counseling on students' mathematical attitudes and self-regulated learning ability. The results of mentoring applied to mathematics learning counseling had a positive effect on reinforcing prerequisite learning, improving self-regulated learning ability, strengthening mathematical strategies, and inducing learning motivation and maintaining interest. We are looking forward to that men-tutoring can be used effectively for students who have difficulty learning mathematics.
Keywords: mentoring; tutoring; men-tutoring; mathematics learning counseling